Supporting literacy through social justice literature: A conceptual argument for reading time in preservice teaching - Ingersoll, Marcea (Language and Literacy / Langue et littératie, 2024)
Preservice teachers enter teacher education programs with varying reading habits and conceptions of social justice. This specific problem of practice—made visible by personal practical knowledge (Connelly & Clandinin, 1988), is examined using currere (Pinar, 2020) and Simpson and Cremin’s (2022) concept of the additive trio. This conceptual paper asserts the need to simultaneously support preservice teachers’ reading habits, knowledge of children’s literature, and understandings of social justice by allocating preservice curriculum time toward this purpose. It also reveals the hidden curricular labour required to respond to a problem of practice.